Increased intracranial blood flow velocity following mechanical thrombectomy in treatment of acute stroke precedes reocclusion. Issue 4 (19th September 2021) - Lauerer, Markus; Wunderlich, Silke; Boeckh‐Behrens, Tobias; Ikenberg, Benno
Abstract: Rising numbers of mechanical thrombectomies in treatment of acute stroke emphasize the need for appropriate follow‐up to identify potential complications in time. Recent findings suggest that abnormal hemodynamics post‐recanalization are associated with worse outcomes. Here, we present the case of a patient who exhibited an increased blood flow velocity on transcranial color‐coded duplex sonography (TCCD) following endovascular intervention shortly before suffering a reocclusion of the recanalized vessel. Our example shows that TCCD may serve as a valuable tool for detecting patients at risk for secondary vascular events after mechanical thrombectomy. Abstract : (A) Time‐of‐flight (TOF) magnetic resonance (MR) angiography showing vascular irregularities at the former recanalization site 3 days post‐thrombectomy. (B) Increased blood flow velocity (BFV) in the left middle cerebral artery (MCA) was measured by transcranial color‐coded duplex sonography (TCCD) 3 days after mechanical recanalization.